Static and Dynamic Performance of Vector Control on Induction Motor with PID Controller: An Investigation on LabVIEW - Abdillah Aziz Muntashir; Era Purwanto; Bambang Sumantri; Hanif Hasyier FAkhruddin; Raden Akbar Nur Apriyanto (Universitas Muhammadiyah Magelang, 2021)
A three-phase induction motor is often used in everyday life because of its high reliability. However, it is associated with some disadvantages, including difficulties in maintaining constant speed during load changes and speed regulation due to the decoupled system. Therefore, this study aims to adjust the three-phase induction motor control to become a separate amplifier DC motor by setting the vector control using the IFOC method, which changes the coupled to the decoupled system. The speed settings are equipped with a PID controller where its parameters, which are obtained using Ziegler Nichols, produce speed output with fast research time and small steady-state errors. This research was conducted to observe and analyze the performance of a controller based on the IFOC approach with a PID controller at speed differences, with static and dynamic conditions in the entire speed working area. In the first stage of the research, simulation is carried out with static conditions, namely changes in speed variations throughout the work area (low speed to high speed), the next stage is a simulation with dynamic conditions, which is to provide changes in the value of the load torque when the system is operating. The simulation result carried out with LabVIEW shows a response time of 1.13 ms, a settling time of 9.9 ms, and a steady error of 0.4% at the 500 Rpm set point. It also indicated dynamic characteristics with a recovery time of 4.9 ms at the 300 Rpm set point. When operated at low speed, IFOC with PID controller has a stable response. But In dynamic conditions, the use of a PID controller is considered unsuitable. This is because the PID controller is less fast and less robust in responding to the system when conditions change in the value of the load torque.